Sensitivity analysis and thermoeconomic comparison of ORCs (organic Rankine cycles) for low temperature waste heat recovery. (15th March 2015) - Feng, Yongqiang; Zhang, Yaning; Li, Bingxi; Yang, Jinfu; Shi, Yang
Abstract: The sensitivity analysis for low temperature ORCs (organic Rankine cycles), as well as the thermoeconomic comparison between the basic ORC and regenerative ORC using Non-dominated sorting genetic algorithm-II (NSGA-II), are conducted in this paper. The derivatives of five system parameters on system performance are used to evaluate the parametric sensitiveness. The exergy efficiency and the APR (heat exchanger area per unit net power output) are selected as the objective functions for multi-objective optimization using R123 under the low temperature heat source of 423 K. The Pareto frontier solution with bi-objective for maximizing exergy efficiency and minimizing APR is obtained and compared with the corresponding single-objective solutions. The results indicate that the prior consideration of improving thermal efficiency and exergy efficiency is to increase the evaporator outlet temperature. A fitting curve can be yielded from the Pareto frontier between the thermodynamic performance and economic factor. The optimum exergy efficiency and APR of the regenerative ORC obtained from the Pareto-optimal solution are 59.93% and 3.07 m 2 /kW, which are 8.10% higher and 15.89% lower than that of the basic ORC, respectively. The Pareto optimization compromises the thermodynamic performance and economic factor, therefore being more suitable for decision making. Highlights: The sensitivity analysis of the basic ORC is conducted. The Pareto-optimal solution is compared with the single-objective solutions. Evaporator outlet temperature should be preferentially considered. 8.10% higher exergy efficiency and 15.89% lower APR for the regenerative ORC.